IMPROVING USER EXPERIENCE THROUGH GREENPEACE WEBSITE UI/UX REDESIGN WITH THINKING DESIGN METHOD - Saefudin, Mohamad; Sudjiran, Sudjiran; Mawarti, Meilyana Anisa (Journal of Information System, Informatics and Computing, 2023)
Greenpeace, an organization dedicated to addressing environmental concerns, particularly the Climate Crisis, urges both the government and corporations to take responsibility for extensive land clearing for business purposes without implementing preventive measures. This lack of action poses potential negative consequences for Indonesia, especially in the economic sector. Despite ongoing issues arising from the Climate Crisis, there is still a dearth of government initiatives and community support. To address this, Greenpeace employs its website as an informational platform, providing details about areas impacted and the actions it takes to improve the Earth. In an effort to enhance the user experience in navigating Greenpeace's activities, the author and their team undertook a redesign of the website using Design Thinking as a method. Design Thinking, a problem-solving process centered on user interests and innovation, involves stages such as empathizing, defining, ideating, prototyping, and testing. The author mapped out problems during the empathize stage based on user experiences, defined core user issues in the define stage, expressed solutions in the ideate stage, implemented web design in the prototype stage, and, in the testing stage, assessed the success of the design in resolving problems and meeting user needs. The research outcomes are presented in the form of a prototype with a UI/UX design, developed by aligning with user needs through the Design Thinking method to provide a solution for user challenges when interacting with the Greenpeace website.